Corrosion Inhibition and Adsorption Properties of Ethanolic Extract of Calotropis for Corrosion of Aluminium in Acidic Media. (5th March 2013) - Kumar, Sudesh; Mathur, Suraj Prakash
Abstract : The corrosion inhibition of aluminium in sulfuric acid solution in the presence of different plant parts, namely, leaves, latex, and fruit was studied using weight loss method and thermometric method. The ethanolic extracts of Calotropis procera and Calotropis gigantea act as an inhibitor in the acid environment. The inhibition efficiency increases with increase in inhibitor concentration. The plant parts inhibit aluminium, and inhibition is attributed, due to the adsorption of the plant part on the surface of aluminium.